Formulation Techniques of Organizational Strategies in Jakarta (Case Study: Insurance Companies in Jakarta) - Suryawan, Ian Nurpatria; Yulisnada, Yulisnada; Mardony, Denyus; Lukito, Jefri (Universitas Pelita Harapan, 2021)
Strategy becomes important for every organization to win competition through changes in internal and external environmental factors. Strategy requires strength, effort and good analysis to anticipate each challenge. Pearce and Robinson explain the stages of strategy management that produce strategy formulation techniques so that the strategies made by the organization are directed and correct. The method used in this research is discussion of qualitative descriptive research through proof of research that has been carried out by previous researchers regarding strategy. The results is business competitions in insurance products nowadays need to be responded by providing the best possible service therefore the insurance products are increasingly demanded by customers in this globalization era which is marked by rapid positive and negative impact on the organization. Thus, it is necessary to be careful in managing every organizational resources, not only focusing on internal organizational factors, but also external factors by utilizing any opportunities or threats that affect the organization both directly and indirectly. The CEOs of insurance company require to make analysis and formulation techniques to apply strategies in the form of winning competition and creating competitive advantage.